Determinant Employee Performance and Job Satisfaction: Analysis Motivation, Path Career and Employee Engagement in Transportation and Logistics Industry - Primadi Candra Susanto; Ni Nyoman Sawitri; Sugeng Suroso (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the effect between variables in this study. The results showed that there was no positive and significant partial effect of Employee Performance on Job Satisfaction. This can be interpreted that the perception of Employee Performance has not been able to work on employee job satisfaction. However, there is a simultaneous positive and significant effect of Motivation, Career, Employee Engagement, and Employee Performance on employee Job Satisfaction. This can be interpreted that higher perceptions of Motivation, Career, Employee Engagement, and Employee Performance can increase employee Job Satisfaction. This research uses quantitative methods and path analysis of the SPSS Version 22 program, a sample of 58 people from various representative transportation and logistics companies.